If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4-4x=6x-6
We move all terms to the left:
-4-4x-(6x-6)=0
We get rid of parentheses
-4x-6x+6-4=0
We add all the numbers together, and all the variables
-10x+2=0
We move all terms containing x to the left, all other terms to the right
-10x=-2
x=-2/-10
x=1/5
| 2(x+7)-3+5x=4x+3x+11 | | x−4+1=−3−x | | -19h+12=-14h-8 | | 8x-7(-5)=-3 | | 1/2x-2/3x=3 | | 1/2×-4+1=-3-1/2x | | x2+12x+6=0 | | 21=2m+8+1 | | 10x-43=39+(x-10) | | 12=-n+4n | | 2(c-6)=9+2 | | 16/8=x/1 | | (3x^2-x-52)=0 | | 3x2+x+1=−5x | | 11/n=85 | | x-1/2(-4)=3 | | 5−2(x+6)=14 | | (x-2)-3(x-3)+4(2x-7)=18 | | -19=45-8x | | (n(n-3)/2)=10n | | 5x+2(x+4=64 | | -6x-75=45 | | -73=152+15x | | 7(3x+10)-90=223 | | 3(x-2)=5(2-x)+1 | | 24=-3x-36 | | t/8-5=-3 | | 3/4(8+12y)=3 | | 4^-3=8x-6 | | 4x+9=3-12 | | (6)/(x+2)=(3)/(4) | | -7+k=20 |